Microbial Reduction of Chromate in the Presence of Nitrate by Three Nitrate Respiring Organisms - Chovanec, Peter; Sparacino-Watkins, Courtney E.; Zhang, Ning; Basu, Partha; Stolz, John (Frontiers in Microbiology, 2012)
A major challenge for the bioremediation of toxic metals is the co-occurrence of nitrate, as it can inhibit metal transformation. Geobacter metallireducens, Desulfovibrio desulfuricans, and Sulfurospirillum barnesii are three soil bacteria that can reduce chromate (Cr(VI)) and nitrate, and may be beneficial for developing bioremediation strategies. All three organisms respire through dissimilatory nitrate reduction to ammonia (DNRA), employing different nitrate reductases but similar nitrite reductase (Nrf). G. metallireducens reduces nitrate to nitrite via the membrane bound nitrate reductase (Nar), while S. barnesii and D. desulfuricans strain 27774 have slightly different forms of periplasmic nitrate reductase (Nap). We investigated the effect of DNRA growth in the presence of Cr(VI) in these three organisms and the ability of each to reduce Cr(VI) to Cr(III), and each organisms responded differently. Growth of G. metallireducens on nitrate was completely inhibited by Cr(VI). Cultures of D. desulfuricans on nitrate media was initially delayed (48 h) in the presence of Cr(VI), but ultimately reached comparable cell yields to the non-treated control. This prolonged lag phase accompanied the transformation of Cr(VI) to Cr(III). Viable G. metallireducens cells could reduce Cr(VI), whereas Cr(VI) reduction by D. desulfuricans during growth, was mediated by a filterable and heat stable extracellular metabolite. S. barnesii growth on nitrate was not affected by Cr(VI), and Cr(VI) was reduced to Cr(III). However, Cr(VI) reduction activity in S. barnesii, was detected in both the cell free spent medium and cells, indicating both extracellular and cell associated mechanisms. Taken together, these results have demonstrated that Cr(VI) affects DNRA in the three organisms differently, and that each have a unique mechanism for Cr(VI) reduction.